2013
DOI: 10.1007/s10484-013-9224-7
|View full text |Cite
|
Sign up to set email alerts
|

Foveal and Peripheral Fields of Vision Influences Perceptual Skill in Anticipating Opponents’ Attacking Position in Volleyball

Abstract: The importance of perceptual-cognitive expertise in sport has been repeatedly demonstrated. In this study we examined the role of different sources of visual information (i.e., foveal versus peripheral) in anticipating volleyball attack positions. Expert (n = 11), advanced (n = 13) and novice (n = 16) players completed an anticipation task that involved predicting the location of volleyball attacks. Video clips of volleyball attacks (n = 72) were spatially and temporally occluded to provide varying amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 42 publications
0
14
0
2
Order By: Relevance
“…They had to evaluate the representativeness of the sequences on a Likert type scale ranging from 0 ( not representative ) to 7 ( perfectly representative ). The 10 sequences of each type (total of 50) with the highest average scores were kept for the experimentation (for a similar selection method, see 39 , 40 ). Before the experiment, sequences were randomized, but all participants viewed the sequences in the same order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They had to evaluate the representativeness of the sequences on a Likert type scale ranging from 0 ( not representative ) to 7 ( perfectly representative ). The 10 sequences of each type (total of 50) with the highest average scores were kept for the experimentation (for a similar selection method, see 39 , 40 ). Before the experiment, sequences were randomized, but all participants viewed the sequences in the same order.…”
Section: Methodsmentioning
confidence: 99%
“…Fixations occurring outside the identified AOIs corresponded to “elsewhere”. A region was considered fixed if the angular velocity of the eyes relative to the stimuli was 30°/s or less for at least 100 ms 39 , 41 . Number of fixations, fixation time, AOI fixated and the moment of fixation of those AOIs were measured.…”
Section: Methodsmentioning
confidence: 99%
“…In this setting, the wizard observed the confederate and the robot from the same room. Thus, the human observer could have subconsciously interpreted subtle cues in the motion patterns of the confederate that the robotic recognizers are not able to interpret reliably, e.g., by observing the motion preceding an attack in volleyball ( Schorer et al, 2013 ) or a penalty kick in football ( Noël et al, 2014 ), athletes can anticipate the actions of their opponents (also see Abernethy et al, 2007 ). This is more pronounced in everyday behaviors of groups as they tend to synchronize by subtly communicating their next movements to each other ( Néda et al, 2000 ; Richardson et al, 2007 ; Lakens and Stel, 2011 ).…”
Section: Related Workmentioning
confidence: 99%
“…The goal of this form of visual perception training is to accelerate the process of performance development, bringing the perceptual abilities of a novice up to expert level as quick as possible [ 24 ]. Video-based studies frequently use the temporal occlusion technique [ 3 , 8 , 25 , 26 , 27 ] where sport-specific video sequences are interrupted at a certain time, leaving subjects to anticipate the actual outcome of the scene. It has been shown that the perspective of the videos shown can affect the learning rate and, therefore, such videos are typically presented from the “first-person” perspective ( i.e.…”
Section: Introductionmentioning
confidence: 99%